2009
DOI: 10.1186/1756-0500-2-174
|View full text |Cite
|
Sign up to set email alerts
|

MRI assessment of cortical thickness and functional activity changes in adolescent girls following three months of practice on a visual-spatial task

Abstract: Background:Neuro-imaging studies demonstrate plasticity of cortical gray matter before and after practice for some motor and cognitive tasks in adults. Other imaging studies show functional changes after practice, but there is not yet direct evidence of how structural and functional changes may be related. A fundamental question is whether they occur at the same cortical sites, adjacent sites, or sites in other parts of a network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
119
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 30 publications
16
119
0
3
Order By: Relevance
“…This suggests that the age-related functional changes are not purely consequences of structural maturation and may reflect the maturation of neurocognitive strategies. Consistent with these results, a recent study of visuospatial training in adolescent girls revealed that cortical thickness increases and brain activation changes after training did not occur in the same brain regions (Haier et al, 2009).…”
Section: Discussionsupporting
confidence: 75%
“…This suggests that the age-related functional changes are not purely consequences of structural maturation and may reflect the maturation of neurocognitive strategies. Consistent with these results, a recent study of visuospatial training in adolescent girls revealed that cortical thickness increases and brain activation changes after training did not occur in the same brain regions (Haier et al, 2009).…”
Section: Discussionsupporting
confidence: 75%
“…65 The authors focused on cortical thickness measures but found no increase in DLPFC or HC, but in frontal eye fields and the temporal pole. This suggests that the structural growth of HC and DLPFC may be unique for the game genre used in this study.…”
Section: Limitationsmentioning
confidence: 99%
“…While it is not currently known precisely how much time is needed to facilitate structural changes (i.e., improvements) in the brain due to exercise, it is reasonable to hypothesize that relatively short-term structural change may be possible. In two separate studies demonstrating brain plasticity, as little as 1.5 to 3 months of cognitive training resulted in cortical changes in younger populations (Driemeyer et al, 2008;Haier et al, 2009). As for exercise, six months of aerobic exercise using moderate intensity walking 3 days per week www.intechopen.com for an hour each session not only prevented brain volume atrophy but resulted in brain volume improvement in older adults (Colcombe et al, 2006).…”
Section: Voxel-wise or Roi Approach?mentioning
confidence: 99%